Prolonged systemic inflammation persistently modifies synaptic plasticity in the hippocampus: modulation by the stress hormones - Maggio, Nicola; Shavit-Stein, Efrat; Dori, Amir; Blatt, Ilan; Chapman, Joab (Frontiers in Molecular Neuroscience, 2013)
Transient systemic inflammation has been shown to cause altered behavior both in humans and in laboratory animals through activation of microglia and heightened level of cytokines detected in the brain and in the body. Furthermore, both activated microglia and the increased cytokines level have been associated with the sudden clinical deterioration in demented people or in aged patients upon systemic inflammation. Whilst it is increasingly becoming clear the role of transient systemic inflammation in promoting dementia in aged individuals, it is still a matter of debate whether prolonged systemic inflammation might persistently modify the brain. In this study, we examined the influence of a systemic long term inflammatory event on synaptic plasticity. We report that while a short exposure to LPS produces transient deficit in long term potentiation (LTP) expression, systemic prolonged inflammation impairs LTP in slices of animals previously primed by a Complete Freund’s adjuvant injection. Interestingly, steroids are able to modulate this effect: whereas glucocorticosteroid (GR) activation further reduces LTP, mineralocorticosteroid receptors (MR) activation promotes the full recovery of LTP. We believe that this research advances the current understandings on the role of the immune system in the onset and progression of cognitive deficits following long lasting systemic inflammation, and proposes possible insights on future strategies in order to prevent early dementia in these predisposed individuals.